The Effect of Fiscal Decentralization on Accountability with Corruption Prevention as A Moderating Variable: Study on Local Governments in Districts/Cities in Central Sulawesi - Balgis, Balgis; Muhammad DIN; Ridwan, Ridwan; Parwati, Ni Made Suwitri (Balance : Jurnal Akuntansi dan Manajemen, 2025)
This study aims to analyze the effect of fiscal decentralization on accountability, with a focus on corruption prevention as a moderating variable, in the context of district / city governments in Central Sulawesi Province. Fiscal decentralization gives more authority to local governments in the management of financial resources, which is expected to increase the independence and efficiency of local budget management. However, without effective oversight mechanisms, fiscal decentralization has the potential to exacerbate corrupt practices at the local government level. In this study, accountability is identified as a key factor to ensure transparency in the implementation of fiscal decentralization, thereby reducing opportunities for corruption. The method used in this study is a quantitative approach with regression analysis, which combines financial data and survey outcomes from local officers in Central Sulawesi. It is expected that the results of this study will provide in-depth insight into the role of corruption prevention in moderating the relationship between fiscal decentralization and accountability, as well as generate policy recommendations to strengthen corruption-free and transparent governance in the local government. This research is intended to be a reference for policy makers in an effort to improve the effectiveness of fiscal decentralization in preventing corruption in local governments.